Malignancy after gastrointestinal augmentation in childhood - Douglas A. Husmann (Therapeutic Advances in Urology, 2009)
Introduction: To review the incidence and risks of bladder cancer following gastrointestinal augmentations done for congenial anomalies in childhood. Materials and Methods: A literature search using PubMed and Ovid Medline search engines was performed. MeSH terms evaluated were; bladder augmentations, enterocystoplasty, gastrocystoplasty, spina bifida, spinal dysraphism, myelodysplasia, neural tube defects, posterior urethral valves and bladder exstrophy were cross referenced with the terms, bladder cancer and urinary bladder neoplasm. All patients who developed a bladder cancer following a bladder augmentation for a congenital anomaly were reviewed Results: A total of 20 cases of bladder cancer following augmentations for congential anomalies, were identified, 9 arose following ileal cystoplasty, 3 following colocystolasty and 8 following gastrocystoplasty. The incidence of cancer developing per decade following surgery was 1.5% for ileal/colonic and 2.8% for gastric bladder augmentations. The majority of cancers developing within the augmented bladder are at advanced stages at the time of diagnosis (60%; 12/20 cases were ≥T3 at diagnosis). Several of the cases that developed occurred in patients exposed to known carcinogenic stimuli and/or arose in bladders with a known predisposition to carcinoma. Conclusion: Patients augmented with ileal or colonic segment for a congenital bladder anomaly have a 7—8 fold and gastric augments a 14—15 fold increased risk for the development of bladder cancer over standard norms. Published data is however unable to determine if gastrointestinal bladder augmentation is an independent risk factor for cancer over the inherent risk of cancer arising from a congenitally abnormal bladder.